2000
DOI: 10.1164/ajrccm.162.3.9910118
|View full text |Cite
|
Sign up to set email alerts
|

Bone Density, Body Composition, and Inflammatory Status in Cystic Fibrosis

Abstract: Low body weight and loss of bone mass are major problems in adults with cystic fibrosis (CF) and chronic pulmonary infection. Although these complications probably have a multifactorial origin, we hypothesized that the continuous acute-phase inflammatory and catabolic state may contribute. We determined body composition, bone turnover, physical activity, and circulating interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-alpha), and their soluble receptors in 22 adults with CF and 22 age- and sex-matched he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
96
2
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(116 citation statements)
references
References 31 publications
14
96
2
4
Order By: Relevance
“…Many of the comorbidities, including low skeletal muscle mass and function [2] and osteoporosis [3], would be expected to occur in a comparatively older population as part of physiological ageing, yet are evident in patients with CF in their second and third decade of life. Similar comorbidities are a feature of other disorders with a chronic systemic inflammatory component, such as rheumatoid arthritis and chronic obstructive pulmonary disease (COPD), where there is again apparent dissociation of physiological and chronological ageing [4][5][6].…”
mentioning
confidence: 99%
“…Many of the comorbidities, including low skeletal muscle mass and function [2] and osteoporosis [3], would be expected to occur in a comparatively older population as part of physiological ageing, yet are evident in patients with CF in their second and third decade of life. Similar comorbidities are a feature of other disorders with a chronic systemic inflammatory component, such as rheumatoid arthritis and chronic obstructive pulmonary disease (COPD), where there is again apparent dissociation of physiological and chronological ageing [4][5][6].…”
mentioning
confidence: 99%
“…A longitudinal study of BMD in CF patients concluded that both reduced bone accretion and accelerated bone loss contribute to the reduced BMD [8]. Elevated levels of bone turnover markers, including serum osteocalcin, urinary N-telopeptide and bonespecific alkaline phosphatase, have been reported in CF patients [5,6,9,10], and it has been suggested that, in CF, there is an imbalance between bone formation and bone resorption in favour of resorption [11,12]. An association between reduced 25-hydroxyvitamin D levels and reduced BMD has been reported in CF patients [7].…”
mentioning
confidence: 99%
“…An association between reduced 25-hydroxyvitamin D levels and reduced BMD has been reported in CF patients [7]. Poor nutritional status has also been reported to be associated with reduced BMD [4,5,7,10,13,14]. Delayed puberty has been associated with reduced BMD in some studies [2,15], but, in other studies, age of menarche in females did not correlate with BMD [4,6,7].…”
mentioning
confidence: 99%
“…A massa gorda e o percentual de gordura corporal apresentaram-se sem alterações significantes durante o seguimento (Tabela 3). Estudos que compararam os pacientes a um grupo controle observaram que crianças [51][52][53] , adolescentes 52 e adultos [54][55][56] possuem valores abaixo do recomendado para massa magra e gorda, reforçando a idéia de que, mesmo com a melhora da composição corporal, não são todos os pacientes que conseguem atingir a normalidade, como o observado.…”
Section: Discussionunclassified